2016
DOI: 10.1182/blood.v128.22.3246.3246
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prior Malignancies on Second Malignancies and Survival in MM Patients: A Population-Based Study

Abstract: Background Awareness of second malignancies in patients with multiple myeloma (MM) has been increasing during recent years. We have previously shown that second malignancies are associated with a decreased life expectancy in MM patients. Information regarding prior and second malignancies in MM is limited as these patients are often excluded from clinical trials and previously published results from other groups have been conflicting. In the present study we aimed to evaluate two hypotheses. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In contrast to SPM, less is known about pre‐existing malignancies in MM patients. Studies have shown that solid malignancies are more common prior to MM, and that prostate, breast, gynaecological and gastrointestinal cancer are the most common pre‐existing entities 8‐10 . Both previous cancers and SPM have been shown to have a negative impact on survival in MM patients and a previous cancer diagnosis may increase the risk for SPM 11‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to SPM, less is known about pre‐existing malignancies in MM patients. Studies have shown that solid malignancies are more common prior to MM, and that prostate, breast, gynaecological and gastrointestinal cancer are the most common pre‐existing entities 8‐10 . Both previous cancers and SPM have been shown to have a negative impact on survival in MM patients and a previous cancer diagnosis may increase the risk for SPM 11‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with multiple myeloma diagnosed in Sweden, a prior malignancy diagnosis (PMD) – as a potential proxy for genetic susceptibility to cancer – was associated with SPM development and mortality, as compared to those without a PMD [16]. At present, information on the impact of a PMD on the development of SPMs and mortality among patients with FL is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, with improved survival the risk of developing second cancers becomes more clinically relevant and is further enhanced by some novel life-extending therapies, e.g. the immunomodulatory drug (IMiD) lenalidomide in multiple myeloma (Jones et al, 2016;Jonsdottir et al, 2017). Available published data and our clinical experience suggest that in the era of classical chemotherapy outcome for patients with two active incurable cancers was mostly dismal.…”
mentioning
confidence: 99%